Randomised feasibility study of physiotherapy for patients with functional motor symptoms. Issue 6 (30th September 2016) - Nielsen, G; Buszewicz, M; Stevenson, F; Hunter, R; Holt, K; Dudziec, M; Ricciardi, L; Marsden, J; Joyce, E; Edwards, MJ
Abstract : Objective: To determine the feasibility of conducting a randomised controlled trial of a specialist physiotherapy intervention for functional motor symptoms (FMS). Methods: A randomised feasibility study was conducted recruiting patients with a clinically established diagnosis of FMS from a tertiary neurology clinic in London, UK. Participants were randomised to the intervention or a treatment as usual control. Measures of feasibility and clinical outcome were collected and assessed at 6 months. Results: 60 individuals were recruited over a 9-month period. Three withdrew, leaving 29 intervention and 28 controls participants in the final analysis. 32% of patients with FMS met the inclusion criteria, of which 90% enrolled. Acceptability of the intervention was high and there were no adverse events. At 6 months, 72% of the intervention group rated their symptoms as improved, compared to 18% in the control group. There was a moderate to large treatment effect across a range of outcomes, including three of eight Short Form 36 (SF36) domains (d=0.46–0.79). The SF36 Physical function was found to be a suitable primary outcome measure for a future trial; adjusted mean difference 19.8 (95% CI 10.2 to 29.5). The additional quality adjusted life years (QALY) with intervention was 0.08 (95% CI 0.03 to 0.13), the mean incremental cost per QALY gained was £12 087. Conclusions: This feasibility study demonstrated high rates of recruitment, retention and acceptability. Clinical effect size was moderate to large with high probability of being cost-effective. A randomised controlled trial is needed. Trial registration number: NCT02275000 ; Results.